Drosophila GFAT1 and GFAT2 enzymes encode obligate developmental functions. Issue 1 (1st October 2020) - Chen, Po; Visokay, Sarah; Abrams, John M.
ABSTRACT: Glutamine: fructose-6-phosphate amidotransferase (GFAT) enzymes catalyse the first committed step of the hexosamine biosynthesis pathway (HBP) using glutamine and fructose-6-phosphate to form glucosamine-6-phosphate (GlcN6P). Numerous species (e.g. mouse, rat, zebrafish, chicken) including humans and Drosophila encode two broadly expressed copies of this enzyme but whether these perform redundant, partially overlapping or distinct functions is not known. To address this question, we produced single gene null mutations in the fly counterparts of gfat1 and gfat2 . Deletions for either enzyme were fully lethal and homozygotes lacking either GFAT1 or GFAT2 died at or prior to the first instar larval stage. Therefore, when genetically eliminated, neither isoform was able to compensate for the other. Importantly, dietary supplementation with D-glucosamine-6-phosphate rescued GFAT2 deficiency and restored viability to gfat2 −/- mutants. In contrast, glucosamine-6-phosphate did not rescue gfat1 −/- animals.